Perinatal Maternal Stress and Susceptibility to Infectious Diseases in Later Childhood: An Early Life Programming Perspective. Issue 1 (2nd January 2019) - Stepanikova, Irena; Baker, Elizabeth; Oates, Gabriela; Acharya, Sanjeev; Uddin, Jalal; Thon, Vojtech; Svancara, Jan; Kukla, Lubomir
Abstract: There is evidence of transmission of stress-related dysregulation from parents to offspring during early developmental stages, leading to adverse health outcomes. This study investigates whether perinatal stress is linked to the risk of infectious diseases in children aged 7–11 years. We hypothesize that stress exposure during pregnancy and the first 6 months after birth independently predict common infectious diseases. Data are obtained from ELSPAC-CZ, a prospective birth cohort. Maternal stress, operationalized as the number of life events, is examined for pregnancy and the first 6 months postpartum. Children's diseases include eye infection, ear infection, bronchitis/lung infection, laryngitis, strep throat, cold sores, and flu/flu-like infection. More prenatal and postnatal life events are both independently linked to a higher number of infectious diseases between the ages of 7–11 years. The effect is larger for postnatal vs. prenatal events, and the effect of prenatal events is attenuated after maternal health in pregnancy is controlled. The results suggest that perinatal stress is linked to susceptibility to infectious diseases in school-age children. Interventions to address stress in pregnant and postpartum women may benefit long-term children's health.